Case series of Rapidly growing Mycobacterial Post-operative surgical site infection in kidney transplant recipients. (2022) - Masalmani, Muna Al; Hashim, Samar Mahmoud A.; Ittaman, Ajithkumar; Abu Jarir, Sulieman S.; Abukhattab, Mohammed; Soub, Hussam Al; Suwaidi, Zubaida Al; Fadhil, Riyadh; Ali, Omar
Abstract: Background: Case series of Rapidly growing Mycobacterial Post-operative wound infection with Mycobacterium Abscessus and/or Mycobacterium Chelone in 4 cases of kidney transplant adult recipient who presented within 6 months of transplant . Case presentations: We report 4 cases of Renal transplant recipients with post-surgical site infection with NTM-69-year-old with post-surgical wound infection with microbiologically proven Mycobacterium Abscessus who discontinued treatment and further presented with intra-abdominal abscess. Next case was 61 years male presented with nodular swellings at surgical site with US findings of intra-abdominal muscle abscess was tested culture positive for Mycobacterium Chelonae and Abscessus.Third case was 34 years male presented with surgical wound infection which was positive for AFB by ZN stain. Lastly, 46 years old male patient known hypertensive and E.S.R.D, had culture proven Mycobacterium Abscessus surgical wound infection. All the four cases had their renal transplant at Philippines at different centres. Conclusions: Nontuberculous mycobacteria infection is important cause of morbidity in kidney transplant recipient and high index of suspicion with early diagnosis and treatment is crucial for successful outcome.